Tramoya or vocation - Salvadé, Romina (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2023)
The work proposes the category of the public as an axis to anthropologically analyze the way in which the denial of interest is emblematized in organizations that are defined as non-profit and whose tasks are oriented towards the public good. The native perspective of those who invoke the non-profit is recovered, understood as renouncing private profit in favor of the common good, to analyze how it operates on participation in public life from these organizations. From this analysis it is revealed that the native opposition between “tramoya” and “vocation” is key to understanding what model of the public is reflected behind the invocation of the non-profit. The empirical cut includes different non-profit organizations in the city of Olavarría, province of Buenos Aires, during the period 2013-2020. The analysis material is made up of ethnographic interviews, observation records and material recovered from different local media.